2017
DOI: 10.1038/s41598-017-12353-z
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal arterial-venous fusions and fate specification in mouse embryos lacking blood flow

Abstract: The functions of blood flow in the morphogenesis of mammalian arteries and veins are not well understood. We examined the development of the dorsal aorta (DA) and the cardinal vein (CV) in Ncx1 −/− mutants, which lack blood flow due to a deficiency in a sodium calcium ion exchanger expressed specifically in the heart. The mutant DA and CV were abnormally connected. The endothelium of the Ncx1 −/− mutant DA lacked normal expression of the arterial markers ephrin-B2 and Connexin-40. Notch1 activation, known to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Supporting this point, loss of systemic blood flow in chick 13, 14 and mice 15, 16 produces defects in arteriovenous specification and induces AVMs. For example, in Ncx1 −/− mouse embryos (which lack a heartbeat), blood flow is not required for initial formation of the dorsal aorta and the cardinal vein but is necessary to induce separation of these vessel structures and to maintain arterial marker expression and suppress venous identity genes in the dorsal aorta 15 . Thus, early endothelial cell fate acquisition is dynamic, and hemodynamic signaling is needed to sustain arteriovenous identity in the remodeling vasculature.…”
Section: Role Of Shear Stressmentioning
confidence: 88%
“…Supporting this point, loss of systemic blood flow in chick 13, 14 and mice 15, 16 produces defects in arteriovenous specification and induces AVMs. For example, in Ncx1 −/− mouse embryos (which lack a heartbeat), blood flow is not required for initial formation of the dorsal aorta and the cardinal vein but is necessary to induce separation of these vessel structures and to maintain arterial marker expression and suppress venous identity genes in the dorsal aorta 15 . Thus, early endothelial cell fate acquisition is dynamic, and hemodynamic signaling is needed to sustain arteriovenous identity in the remodeling vasculature.…”
Section: Role Of Shear Stressmentioning
confidence: 88%
“…In contrast to EMPs, these lymphoid progenitors arise from HE with arterial characteristics (Yzaguirre and Speck, 2016), suggesting important roles for arterial endothelial niche and hemodynamic forces in the specification of hematopoietic cells with lymphoid potential. Supporting this association, Notch1 signaling, which plays an essential role in arterial endothelial specification (Lawson et al, 2001;Corada et al, 2014) and stabilization of arterial transcriptional programs in response to blood flow (Lawson et al, 2001;le Noble et al, 2004;Hwa et al, 2017;Weijts et al, 2018), is required for multilineage hematopoiesis and HSC development in vivo (Kumano et al, 2003;Hadland et al, 2004) and has been shown to play a role in conferring lymphocyte potential to nascent stem/progenitor cells derived during the differentiation of pluripotent stem cells (Lu et al, 2016;Uenishi et al, 2018). The role of Notch signaling and blood flow hemodynamics in the emergence of multilineage hematopoiesis and HSCs will be discussed in more detail in the following section, "HSC Development in the Arterial Vascular Niche" of this review.…”
Section: The First Lymphoid Progenitors Arise From Hemogenic Endothelmentioning
confidence: 99%
“…In both the sih −/− zebrafish and the Ncx1 knockout, embryos lacked endocardial cushion development, while looping and chamber specification remained unaffected (Koushik et al, 2001; Sehnert et al, 2002; Bartman et al, 2004). Studies with sih −/− zebrafish and Ncx1 knockout mice support the idea that endocardial cushion development is exquisitely sensitive to changes in myocardial function (Koushik et al, 2001; Bartman et al, 2004; Bartman and Hove, 2005; Hwa et al, 2017).…”
Section: Altering Hemodynamic Conditions In Animal Models: Lessonsmentioning
confidence: 83%
“…Mouse and zebrafish models have been used extensively for genetic manipulations, and transgenic lines are widely available for both species (Koushik et al, 2001; Huang et al, 2003; Hwa et al, 2017). Transgenic lines that express fluorescent probes driven by a chosen promoter have been widely used both for visualization and lineage studies, and are often bred into other mutant lines to augment analysis (Auman et al, 2007; Zhang et al, 2014; Samsa et al, 2015; Lee et al, 2016; Battista et al, 2017).…”
Section: Altering Hemodynamic Conditions In Animal Models: Lessonsmentioning
confidence: 99%